Design and implementation of an African native language-based programming language - John. B. Oladosu; Odetunji A. Odejobi; Stephen O. Olabiyisi; Ezekiel K. Olatunji (International Journal of Advances in Applied Sciences, 2021)
Most of the existing high-level programming languages have hitherto borrowed their lexical items from human languages including European and Asian languages. However, there is a paucity of research information on programming languages developed with the lexicons of an African indigenous language. This research explored the design and implementation of an African indigenous language-based programming language using Yoruba as a case study. Yoruba is the first language of over 30 million people in the southwest of Nigeria, Africa; and is spoken by over one hundred million people worldwide. It is hoped, as established by research studies, that making computer programming possible in one’s mother tongue will enhance computer-based problem-solving processes by indigenous learners and teachers. The alphabet and reserved words of the programming language were respectively formed from the basic Yoruba alphabet and standard Yoruba words. The lexical items and syntactic structures of the programming language were designed with appropriate regular expressions and context-free grammar, using Backus-Naur form (BNF) notations. A prototype implementation of the programming language was carried out as a source-to-source, 5-pass compiler. QBasic within QB64 IDE was the implementation language. The results from implementation showed the functional correctness and effectiveness of the developed programming language. Thus, lexical items of a programming language need not be borrowed exclusively from European and Asian languages, they can and should be borrowed from most African native languages. Furthermore, the developed native language programming language can be used to introduce computer programming to indigenous pupils of primary and junior secondary schools.